Seleksi Lapang Ketahanan Beberapa Varietas Padi terhadap Infeksi Hawar Daun Bakteri Strain IV dan VIII - Lina Herlina; Tiur S. Silitonga (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2011)
Field Selection on Several Rice Varieties for Resistance to Bacterial Leaf Blight strain IV and VIII. Bacterial leaf blight (BLB) on rice (Oryza sativa) caused by Xanthomonas oryzae pv. oryzae (Xoo) is the major obstruction for rice production. Powerful strategy to control BLB is generally conducted by planting resistant plant. Meanwhile, the main way to explore germplasm as the source of resistance gene is conducted by selection a wide rice varieties. Field selection for resistance to BLB on 150 rice-varieties (BB-Biogen collection) was conducted in 2009 in Cianjur. Three leaves and flag leaves of individual hills at vegetative and flowering stage were inoculated by clipping the leaf tip with scissors which had been connected with a suspension bottle of bacterial cells (109- 1010 cells/ml) of the isolates which represented bacterial groups (strain) IV and VIII, respectively. Each plant was inoculated with one race. Two weeks after inoculation, length of the lesion developed on the inoculated leaf was measured, as an index of severity of infection by BLB. This experiment was treated as Factorial-Randomized Completed Block Design (two factor-with 3 replications, respectively). The resistancyreaction to strain IV and VIII was observed as the variable tested, while the factors measured consists of plant-varieties and two bacterial strains. The results showed that 11 varieties with a resistance-reaction to Xoo strain IV, inwhich 5 varieties poses a consistent resistance-reaction, i.e: Pulu Bolong, Pelopor, Gombal, Barito and Kapuas. While resistancereaction to Xoo strain VIII obtained only one variety : IR42 (score-1), while 17 others showed intermediate resistancy (score-3). AbstrakPenyakit hawar daun bakteri (HDB) yang disebabkan oleh Xanthomonas oryzae pv. oryzae (Xoo) pada padi (Oryza sativa) merupakan faktor pembatas upaya peningkatan produksi padi. Pencarian gen-gen tahan terhadap HDB sangat diperlukan untuk pengendalian penyakit tersebut. Seleksi ketahanan terhadap HDB dilakukan di Cianjur pada MT 2009 terhadap 150 varietas padi koleksi Bank Gen, BB-Biogen. Isolat Xoo yang diuji adalah strain IV dan VIII. Inokulasi dilakukan dua kali, yaitu pada fase vegetatif dan generatif dengan cara menggunting 3-5 cm dari ujung daun dan daun bendera dengan gunting yang telah dihubungkan dengan botol berisi suspensi Xoo strain IV dan VIII (109-1010 sel/ml). Rancangan percobaan yang digunakan dalam penelitian ini adalah acak kelompok faktorial dengan tiga ulangan. Sebagai varietas pembanding tahan digunakan IRBB7 dan pembanding rentan varietas Kencana Bali. Reaksi ketahanan tertinggi terhadap Xoo strain IV ditunjukkan oleh 11 varietas terpilih dengan reaksi agak tahan, lima varietas di antaranya menunjukkan reaksi yang konsisten agak tahan, yaitu varietas Pulu Bolong, Pelopor, Gombal, Barito, dan Kapuas. Reaksi ‘tahan’ terhadap Xoo strain VIII ditunjukkan oleh satu varietas introduksi IR42. Untuk varietas terpilih dengan reaksi ‘agak tahan’ terdapat 17 varietas.